Síntese e caracterização da céria dopada com gadolínio para uso em células combustíveis - Godinho Junior, Mario (2007)
The search for new materials for the development of catalysts, ultraviolet blockers, biomaterials and solid oxide fuel cell as alternative clean energy sources can be directly related to the use of cerium oxide or ceria (CeO2). However, understanding and controlling the synthesis methods, the structural characteristics, as well as some properties, as for instance, the oxygen ionic conductivity of this material, are of great importance to explain or foresee such applications. In this work, the synthesis of the doped ceria with gadolinium performed at room temperature, as well as the polymeric precursor method, have been comparatively used to study the effectiveness of these methods to obtain nanometer order particles. The characterization techniques were X-Ray Diffraction, Raman Spectroscopy, Thermal Analysis, Specific Superficial Area, Scanning Electron Microscopy, Transmission Electronic Microscopy and Impedance Spectroscopy. From obtained results it was possible to evidence the formation of the Ce1-xGdxO1.9-δ phase at room temperature by the coprecipitation method and despite the formation of some agglomerated particles, the homogeneity of the final microstructure was controlled through the study that employed different rate heatings. The attainment of an alternative morphology, for instance nanoribbon, was possible through processing in a hydrothermal system with microwave heating. The electrolyte with particles synthesized by the polymeric precursor method demonstrated a higher intrinsic conductivity, which is the most indicated method for the use in fuels cells.